Abraham in Jewish and early Christian literature - Adams, Sean A.; Domoney-Lyttle, Zanne (Library of second temple studies, 2019)
"Jewish and early Christian authors discussed Abraham in diverse ways, adapting his Old Testament narratives and using Abrahamic imagery in their works. Beginning with a perspective on how Abraham was used within Jewish literature, this collection of essays follow the impact of Abraham across biblical texts, including Pseudigraphic and Apocryphal texts, into early Greek, Latin and Gnostic literature. While some areas of study in Abrahamic texts have received much scholarly attention, other areas remain nearly untouched. The essays build upon the existing scholarship in the area and add to it by discussing Abraham in less-discussed areas such as Abraham in re-written Scripture and contemporary Greek and Latin authors. Through the presentation of a more thorough outline of the impact of the figure and stories of Abraham, the contributors create a more concise and complete idea of how his narrative was employed throughout the centuries, and how ancient authors adopted and adapted received traditions"--